2020
DOI: 10.1093/mnras/staa960
|View full text |Cite
|
Sign up to set email alerts
|

Self-gravitating filament formation from shocked flows: velocity gradients across filaments

Abstract: In typical environments of star-forming clouds, converging supersonic turbulence generates shock-compressed regions, and can create strongly-magnetized sheet-like layers. Numerical MHD simulations show that within these post-shock layers, dense filaments and embedded self-gravitating cores form via gathering material along the magnetic field lines. As a result of the preferred-direction mass collection, a velocity gradient perpendicular to the filament major axis is a common feature seen in simulations. We sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 64 publications
6
40
1
Order By: Relevance
“…Velocity gradients perpendicular to filaments have been found in other clouds as well, e.g. : DR21 (Schneider et al 2010), IRDC 18223 (Beuther et al 2015), Serpens (Dhabal et al 2018;Chen et al 2020) and SDC13 (Williams et al 2018). In these studies, the observed velocity gradients have also found to be possible indications of mass accretion by the filament from inflowing lower-density gas.…”
Section: Continuous Mass Accretion On the Filament Crest In Muscasupporting
confidence: 55%
See 1 more Smart Citation
“…Velocity gradients perpendicular to filaments have been found in other clouds as well, e.g. : DR21 (Schneider et al 2010), IRDC 18223 (Beuther et al 2015), Serpens (Dhabal et al 2018;Chen et al 2020) and SDC13 (Williams et al 2018). In these studies, the observed velocity gradients have also found to be possible indications of mass accretion by the filament from inflowing lower-density gas.…”
Section: Continuous Mass Accretion On the Filament Crest In Muscasupporting
confidence: 55%
“…Here we compare the typical observed relative motions between the crest and the surrounding gas with the expected self-gravity velocities to discuss at which scale gravity may be responsible for the observed relative motions. In Chen et al (2020) it is proposed to use the non-dimensional parameter C ν to differentiate between gravity-driven mass inflow and other sources of motions (shock compression in Chen et al 2020), with C ν expressed as…”
Section: The Physical Scale Of Dominant Self-gravitymentioning
confidence: 99%
“…For example, studies of Serpens south as well as of IRDC 18223 reveal velocity gradients perpendicular to the clouds in some part of the filaments, but in other parts of the clouds these studies find clearly distinct multiple velocity components that may resemble more the subfilament signatures (Fernández-López et al 2014;Dhabal et al 2018;Beuther et al 2015b). Chen et al (2020) point out that multiple velocity-components along a filament do not necessarily always have to be real structures but that the observational bias that different spectral lines trace different density regimes can also create artificial multiple velocity components in observations (see also Ballesteros-Paredes & Mac Low 2002;Zamora-Avilés et al 2017). Different inclination angles and optical depth effects may also induce a similar bias in some data as well.…”
Section: Gas Dynamicsmentioning
confidence: 95%
“…For example, some regions of low and high mass reveal sub-filaments (or fibers) that may collide and form larger-scale filamentary structures during the formation process (e.g., Hacar et al 2013Hacar et al , 2017bHacar et al , 2018Henshaw et al 2014;Smith et al 2014). Other observations have revealed velocity gradients across filaments (e.g., Palmeirim et al 2013;Fernández-López et al 2014;Beuther et al 2015b;Shimajiri et al 2019) that may be explained by gravity-induced accretion from a magnetized sheet-like molecular cloud (e.g., Chen & Ostriker 2015;Chen et al 2020). However, we should keep in mind that in these clouds, often not just one signature exists but that several signatures occur within the same region.…”
Section: Gas Dynamicsmentioning
confidence: 99%
“…3.3 that differences in the synthetic observations based on LTE and non-LTE calculations are clear even for the basic statistics, such as the power spectra and the intensity PDFs. In the ISM context, the non-LTE effects should be important for a wide range of numerical and observational studies of clouds and cores (Walch et al 2015;Padoan et al 2016;Smith et al 2020), filaments, and velocity-coherent structures (Hacar et al 2013(Hacar et al , 2018Arzoumanian et al 2013;Heigl et al 2020;Chen et al 2020;Clarke et al 2020), and the large-scale velocity fields (Burkhart et al 2014;Hu et al 2020). These problems are inherently 3D in nature, require the coverage of a large dynamical range, and are natural applications of line RT modelling on hierarchical grids.…”
Section: Discussionmentioning
confidence: 99%